2018
DOI: 10.1186/s13075-018-1719-4
|View full text |Cite
|
Sign up to set email alerts
|

Blocking CD248 molecules in perivascular stromal cells of patients with systemic sclerosis strongly inhibits their differentiation toward myofibroblasts and proliferation: a new potential target for antifibrotic therapy

Abstract: BackgroundFibrosis may be considered the hallmark of systemic sclerosis (SSc), the end stage triggered by different pathological events. Transforming growth factor-β (TGF-β) and platelet-derived growth factor BB (PDGF-BB) are profibrotic molecules modulating myofibroblast differentiation and proliferation, respectively. There is evidence linking CD248 with these two molecules, both highly expressed in patients with SSc, and suggesting that CD248 may be a therapeutic target for several diseases. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 52 publications
(66 reference statements)
0
27
0
Order By: Relevance
“…9a-d), controlling those fibroblasts may lead to the suppression of fibrosis of IPF. Bartis et al and Benedetto et al demonstrated that the reduction of CD248 expression on the fibroblast cell line via siRNA resulted in the reduction of in vitro cell proliferation [23,26], suggesting that CD248 high-ITGA8 low human fibroblast-like cells are possible candidates as therapeutic targets for IPF lungs. As an anti-fibrotic therapy, CD248 blocking peptide as well as siRNA may be effective tools to suppress the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9a-d), controlling those fibroblasts may lead to the suppression of fibrosis of IPF. Bartis et al and Benedetto et al demonstrated that the reduction of CD248 expression on the fibroblast cell line via siRNA resulted in the reduction of in vitro cell proliferation [23,26], suggesting that CD248 high-ITGA8 low human fibroblast-like cells are possible candidates as therapeutic targets for IPF lungs. As an anti-fibrotic therapy, CD248 blocking peptide as well as siRNA may be effective tools to suppress the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The role of MSCs in injury‐induced tissue fibrosis has been elegantly demonstrated by genetic ablation of Gli1 + MSC, which resulted in the abolishment of fibrosis . Targeting pro‐fibrotic signaling in perivascular stromal cells through inhibition of the C‐type lectin transmembrane receptor Endosialin has recently been shown to inhibit their proliferation and differentiation toward myofibroblasts, which may offer a potential therapeutic target for inhibition of MSC mediated fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…CD248 has also been described as being highly expressed in skin samples of patients with systemic sclerosis in comparison to healthy controls . When CD248 expression was silenced by means of siRNA in mesenchymal stem cells from systemic sclerosis patients, TGF‐β and PDGF profibrotic signalling was reduced.…”
Section: Cd248 In Inflammation and Fibrosismentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis patients also display high expression of CD248 in fibroblasts and it may serve as a disease severity marker [139]. CD248 has also been described as being highly expressed in skin samples of patients with systemic sclerosis in comparison to healthy controls [140]. When CD248 expression was silenced by means of siRNA in mesenchymal stem cells from systemic sclerosis patients, TGF-b and PDGF profibrotic signalling was reduced.…”
Section: Cd248 In Inflammation and Fibrosismentioning
confidence: 99%